The Current Challenges of Scientific Publishing in Medicine: a View From the South - Matusevich, Daniel; Eymann, Alfredo (Revista del Hospital Italiano de Buenos Aires, 2025)
In three years, the editorial landscape has changed radically: the pandemic, AI, and a crisis of scientific trust demand a rethinking of practices. From Latin America, editing science is an ethical, political, and clinical act, requiring care, critical thinking, and commitment to local contexts in the face of global challenges.
Keywords: scientific edition; generative artificial intelligence; Latin America; Indexing